A Rare Case: Intussusception In A 8 -Month-Old-Girl With Intestinal Tuberculosis - Yeni Amalia (JIMR - Journal of Islamic Medicine Research, 2017)
ABSTRACTBackgrounds Intestinal TB can be dif?cult to diagnose due to absence of a particular pattern of symptoms and signs. Definitive diagnosis is based primarily upon histology, Ziehl-Neelsen staining for acid-fast bacilli, and culture.Intussusceptions associated with intestinal TB has been poorly documented in children.Case MA, 8 -month-old girl, weighing 8.4 kg complaining of repetitive vomiting, no flatus and defecation followed by abdominal distention, a solid palpaple mass and increasing of the bowel sounds. Abdominal X-ray showed stepladder signs, edematous intestinal mucosa, no gas distributed in the pelvic area. Abdominal USG revealed a sausage and doughnut signs. An open exploratory laparotomy showed intussusceptions along the ileocaecal region with multiple bands as the lead point. Resection and ileostomy was performed. The pathological ileum sample was revealed a caseosa TB process. The chest Xray showed specific process. The TB score was 6. The patient then administered antituberculosis drug regimen.Conclusion A rare case of intestinal tuberculosis has been successfully diagnosed. In this endemic country of TB, it should be also suspected in patients with intussusception.Keyword : intussusception, intestinal tuberculosis